2000
DOI: 10.4049/jimmunol.164.9.4551
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Experienced CD4 T Cells Display a Reduced Capacity for Clonal Expansion In Vivo That Is Imposed by Factors Present in the Immune Host

Abstract: It is thought that protective immunity is mediated in part by Ag-experienced T cells that respond more quickly and vigorously than naive T cells. Using adoptive transfer of OVA-specific CD4 T cells from TCR transgenic mice as a model system, we show that Ag-experienced CD4 T cells accumulate in lymph nodes more rapidly than naive T cells after in vivo challenge with Ag. However, the magnitude of clonal expansion by Ag-experienced T cells was much less than that of naive T cells, particularly at early times aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 36 publications
9
49
0
Order By: Relevance
“…The residual Ag-specific T cell population is long lasting, but is defective in the ability to proliferate and secrete cytokines upon secondary challenge (85,86). This anergic state of Ag-experienced T cells was shown to require Ag persistence in the immune host environment (86,87) In our study the secondary administration of HEL was able to induce T cell response at the same magnitude observed in the primary HEL response. This nonanergic state of the secondary T cell response may result from the existence of HEL on B cells in the absence of exogenous HEL, thus preserving the naive environment of the recipients.…”
Section: Cd8␣supporting
confidence: 60%
“…The residual Ag-specific T cell population is long lasting, but is defective in the ability to proliferate and secrete cytokines upon secondary challenge (85,86). This anergic state of Ag-experienced T cells was shown to require Ag persistence in the immune host environment (86,87) In our study the secondary administration of HEL was able to induce T cell response at the same magnitude observed in the primary HEL response. This nonanergic state of the secondary T cell response may result from the existence of HEL on B cells in the absence of exogenous HEL, thus preserving the naive environment of the recipients.…”
Section: Cd8␣supporting
confidence: 60%
“…In contrast to this result, Mercia et al (25) found that TCR Tg memory cells proliferated more after transfer to naïve hosts. Our results may differ for several reasons: first, they transferred a large number of TCR Tg cells rather than studying an endogenous CD4 T cell response as we have done.…”
Section: Discussionmentioning
confidence: 44%
“…The ability of IgG to potentiate Ag presentation has been demonstrated in vitro (31)(32)(33)(34)(35) and ex vivo (34,35), and has been implied in vivo (30,36,37). Here, we are able to directly visualize in vivo that IgG2a-mediated feedback enhancement of Ab responses to OVA is preceded by a rapid expansion of specific CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 58%